Randomised clinical trial evaluating the effect of different timing and number of fixed timed artificial inseminations, following a seven‐day progesterone‐based protocol, on pregnancy outcomes in UK dairy heifers. (1st December 2017) - Walsh, John Paul; Coates, Amy; Lima, Fabio; Smith, Rob; Oikonomou, Georgios
Abstract : The objective of this study was to determine the effect on pregnancy outcome of either inseminating heifers twice (at 48 and 72 hours after withdrawal of a controlled internal drug release insert (CIDR) containing progesterone) or once (56 hours after CIDR withdrawal) following a seven‐day CIDR synchronisation protocol. Dairy heifers (n=267) from five farms, with an age range of 388–736 days, were randomly assigned to one of two treatment groups (group A heifers were inseminated twice; group B heifers were inseminated once). Both groups received a CIDR on day (D) 0 and an intramuscular injection of d‐cloprostenol on D6; the CIDR was withdrawn on D7. Measurements of withers height, body condition score and hearth girth (used to estimate weight) were taken on D0. The diameter of the largest follicles and corpora lutea was recorded on both D0 and D6. Data were analysed with the use of multivariable logistic regression modelling. Treatment group and farm were not statistically significantly associated with pregnancy per treatment (P/T). Age and dominant follicle size on D6 were significantly associated with P/T. Heifers with the largest dominant follicle sizes (16–22 mm) were 5.54 times less likely to be pregnant than those heifers with the smallest dominant follicles (8–10 mm) on D6. It was shown that the cost associated with inseminating heifers twice after a seven‐day CIDR synchronisation protocol is not justified.